Patient expectations and willingness to use primary care pharmacy services in the United Arab Emirates. (28th January 2015) - Hasan, Sanah; Sulieman, Hana; Stewart, Kay; Chapman, Colin B; Kong, David C M
Abstract: Objectives: No previous studies have investigated patients' expectations of, or interest in, using primary care pharmacy services in the UAE. The study investigated primary care services that patients would use if they were provided through community pharmacies. Methods: A questionnaire was developed in English and translated to Arabic. Participants were asked to rate their likelihood of using future primary care services on a three-point Likert-type scale (very likely–unlikely). Services included screening for disease, monitoring of disease control, health advice and referral, lifestyle and preventive care, supply of printed information, counselling on medication use and side effects, patient record keeping, and pharmacist intervention in chronic disease. The questionnaire was distributed to patrons of public places by hand to eligible participants: ≥21 years, taking at least one scheduled prescription medication and having adequate Arabic or English proficiency. Key findings: Areas of most interest were as follows: the pharmacist explaining how to use medications (Median = 3, interquartile range (IQR) = 1), the pharmacist advising on side effects of medications (Median = 3, IQR = 1), receiving advice on how to use devices (Median = 3, IQR = 1) and receiving printed information about medications (Median = 3, IQR = 1). Participants were least supportive of pharmacists keeping medication records (Median = 2, IQR = 1) and intervening in chronic disease management (Median = 2, IQR = 1). Participants anticipated a caring professional service by pharmacists and a pharmacy layout that allows private communication. Conclusions: Participants were interested in accessing enhanced primary care services by community pharmacists. Participants were more supportive of receiving information about medications, help in self-management and monitoring, and advice about disease prevention than management of chronic disease.